Reversible Burst of Transcriptional Changes during Induction of Crassulacean Acid Metabolism in Talinum triangulare . Issue 1 (3rd November 2015) - Brilhaus, Dominik; Bräutigam, Andrea; Mettler-Altmann, Tabea; Winter, Klaus; Weber, Andreas P.M.
Abstract : Rapid, reversible induction of Crassulacean acid metabolism (CAM) in conjunction with pronounced reconfiguration of carbon metabolism enables Talinum to survive cycles of severe drought. Abstract: Drought tolerance is a key factor for agriculture in the 21st century as it is a major determinant of plant survival in natural ecosystems as well as crop productivity. Plants have evolved a range of mechanisms to cope with drought, including a specialized type of photosynthesis termed Crassulacean acid metabolism (CAM ). CAM is associated with stomatal closure during the day as atmospheric CO2 is assimilated primarily during the night, thus reducing transpirational water loss. The tropical herbaceous perennial species Talinum triangulare is capable of transitioning, in a facultative, reversible manner, from C3 photosynthesis to weakly expressed CAM in response to drought stress. The transcriptional regulation of this transition has been studied. Combining mRNA-Seq with targeted metabolite measurements, we found highly elevated levels of CAM -cycle enzyme transcripts and their metabolic products in T. triangulare leaves upon water deprivation. The carbohydrate metabolism is rewired to reduce the use of reserves for growth to support the CAM -cycle and the synthesis of compatible solutes. This large-scale expression dataset of drought-induced CAM demonstrates transcriptional regulation of the C3 –CAM transition. We identified candidate transcription factors to mediate this photosynthetic plasticity, which may contribute in the future to the design of more drought-tolerant crops via engineered CAM .